PENGARUH POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Rima Melati; Martono Martono; Antonius Totok Priyadi; Tomo Djudin; Yulis Jamiah (STKIP Persada Khatulistiwa Sintang, 2023)
This research aims to determine the influence of parenting styles self regulated and mathematics learning outcomes for grade IV students at Suster Singkawang Elementary School. The research was carried out using a quantitative approach. The population in this study were fourth grade students at SD Suster Singkawang with a sample of 92 students. The data collection tools used were questionnaires to determine parenting patterns and learning independence, as well as mathematics learning achievement tests. Data analysis was carried out by testing the effect using analysis of variance. Based on the analysis of the data obtained, authoritarian and democratic parenting styles do not have an influence on self regulated because the significance value obtained is more than 5%, while permissive parenting styles have an influence on self regulated with a sig value of <5%. Meanwhile, authoritarian, democratic and permissive parenting styles have a positive influence on students' mathematics learning outcomes.